2016
DOI: 10.1038/srep32730
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and psychiatric disorders: a Mendelian randomization study

Abstract: Obesity is a highly prevalent risk factor for cardiometabolic diseases. Observational studies suggest that obesity is associated with psychiatric traits, but causal inference from such studies has several limitations. We used two-sample Mendelian randomization methods (inverse variance weighting, weighted median and MR-Egger regression) to evaluate the association of body mass index (BMI) with three psychiatric traits using data from the Genetic Investigation of Anthropometric Traits and Psychiatric Genomics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 50 publications
6
47
1
Order By: Relevance
“…In addition, the pleiotropic risk loci were enriched among genes previously associated with neuroticism (corrected enrichment p= 5.28x10 -6 ; GRIK3, CTNND1,DRD2,RGS6,RBFOX1,ZNF804A,L3MBTL2,CHADL,RANGAP1,RSRC1,GRM3), cognitive ability (corrected p= 7.15x10 -5 ; PTPRF, NEGR1, ELOVL3, SORCS3, DCC, CACNA1I), and night sleep phenotypes (corrected p= 1.86x10 -2 ; PBX1, NPAS3, RGS6,GRIN2A,MYO18A,TIAF1,CNTN4,PPP2R2B,TENM2,CSMD1). We also found significant enrichment of pleiotropic risk genes in multiple measures of body mass index (BMI), supporting previous studies suggesting a shared etiologic basis between a range of neuropsychiatric disorders and obesity (Hartwig et al, 2016;Lopresti and Drummond, 2013;Milaneschi et al, 2018)…”
Section: Relationship Between Cross-disorder Genetic Risk and Other Bsupporting
confidence: 89%
“…In addition, the pleiotropic risk loci were enriched among genes previously associated with neuroticism (corrected enrichment p= 5.28x10 -6 ; GRIK3, CTNND1,DRD2,RGS6,RBFOX1,ZNF804A,L3MBTL2,CHADL,RANGAP1,RSRC1,GRM3), cognitive ability (corrected p= 7.15x10 -5 ; PTPRF, NEGR1, ELOVL3, SORCS3, DCC, CACNA1I), and night sleep phenotypes (corrected p= 1.86x10 -2 ; PBX1, NPAS3, RGS6,GRIN2A,MYO18A,TIAF1,CNTN4,PPP2R2B,TENM2,CSMD1). We also found significant enrichment of pleiotropic risk genes in multiple measures of body mass index (BMI), supporting previous studies suggesting a shared etiologic basis between a range of neuropsychiatric disorders and obesity (Hartwig et al, 2016;Lopresti and Drummond, 2013;Milaneschi et al, 2018)…”
Section: Relationship Between Cross-disorder Genetic Risk and Other Bsupporting
confidence: 89%
“…All estimates are reported per 1 SD increase of BMI. The data used in this example are obtained from a published study of Hartwig and coworkers 17. BMI, body mass index; IVW, inverse-variance weighted; ML, maximum likelihood; P-het, Cohrans’s Q p value; SNPs, single-nucleotide polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…The data used in this example are obtained from a published study of Hartwig and coworkers 17. BMI, body mass index; logOR, natural logarithm of OR.…”
Section: Resultsmentioning
confidence: 99%
“…50 Initial Mendelian randomization (MR) studies using weak genetic instruments did not appear to support a causal association between higher BMI and incident depression, 109,110 but one more recent study has suggested a 1.15-fold to 1.40-fold higher risk of depression for each standard deviation increase in BMI. 111 To our knowledge, the inverse association (whether depression causes obesity) has not been assessed in published MR studies to date.…”
Section: Environmental Risk Factors For Obesitymentioning
confidence: 98%